The Influence of US’ Geopolitics in the Latin American Liberation Theology in the Period 1960-1990 - Somiedo García, Juan Pablo (Geopolítica(s). Revista de estudios sobre espacio y poder, 2014)
The article reviews the reasons that led the USA to interpret the new ecclesial movement of Liberation Theology in Latin America as a threat to their interests in the continent and fight it in the political and cultural areas. Correctly understand the causes and derivations of the US stance against implies putting emerging church movement within the broader actors and variables in which the Cold War unfolded and in which Latin America was a more confrontational scenario frame. For its part, the Catholic Church represents, again, the lack of alignment between its politics and its pastoral and evangelical side.
Keywords: geopolitics of religion; international relations; liberation theology; Vatican; Latin America.